Pediatric Pulmonary Alveolar Microlithiasis: A Case Report - Mehrian, Payam (National Research Institute of Tuberculosis and Lung Disease, 2013)
Pulmonary alveolar microlithiasis is a rare infiltrative pulmonary disease characterized by deposition of microliths in the alveoli. In this case report, we present a case of a 5 year-old girl with complaints of common cold and loss of appetite. Chest radiograph showed innumerable small, dense nodules, diffusely involving both lungs. High-resolution CT scan illustrated widespread micro-nodular infiltration, diffuse ground-glass attenuation areas predominantly in upper anterior regions and septal thickening. Trans-bronchial biopsy confirmed the diagnosis.